Alignments in the nobelium isotopes - Zheng Shi-Jie; Xu Fu-Rong; Yuan Cen-Xi; Chong, Qi (Chinese Physics C, 2009)
Total-Routhian-Surface calculations have been performed to investigate the deformation and alignment properties of the No isotopes. It is found that normal deformed and superdeformed states in these nuclei can coexist at low excitation energies. In neutron-deficient No isotopes, the superdeformed shapes can even become the ground states. Moreover, we plotted the kinematic moments of inertia of the No isotopes, which follow very nicely available experimental data. It is noted that, as the rotational frequency increases, alignments develop at ƒßœâ = 0.2‚Ä?.3 MeV. Our calculations show that the occupation of the vj 15/2 orbital plays an important role in the alignments of the No isotopes.